Insecticidal potential of organic extracts of Calotropis procera to Spodoptera frugiperda (Bioscience Journal, 2023)
This study evaluated the toxic effects of organic extracts of Calotropis procera leaves on the survival, development, and reproduction of Spodoptera frugiperda. Solutions of crude methanol extract and hexane and methanol fractions of C. procera leaves were added at 1.15% and 2.14% concentrations to the artificial diet of S. frugiperda. The mortality and duration of larval and pupal phases, weights of female and male pupae, deformations of pupae and adults, the reduction of adults able to reproduce, pre-oviposition and oviposition periods, the number of postures per female, and the fecundity and fertility of S. frugiperda females were also evaluated. The extracts harmed the survival, development, and reproduction of S. frugiperda. The ingestion of extracts and fractions by caterpillars affected adults by decreasing the oviposition period, the number of postures, fecundity, and fertility. The crude MeOH extract at a 2.14% concentration harmed the evaluated parameters of the insect, except for pupal mortality, female pupae weight, and pre-oviposition period. The MeOH fraction at 2.14% caused a 50.0% mortality of caterpillars and 16.0% deformation in pupae and 33.0% in adults, reducing by 72.0% the population able to reproduce. The MeOH fraction at the 2.14% concentration caused 25.0% and 38.0% of pupal mortality and deformation, respectively. Calotropis procera has promising insecticidal properties for a biological insecticide, a convenient and sustainable strategy for protecting plants against S. frugiperda.